Learning at Muhammadiyah 5 Porong Elementary School during the Covid 19 Pandemic - Ranti Nur Fadilah; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study contains various aspects, including: school history, learning during the pandemic, implementation of learning, and the advantages of learning for teachers and students. This study uses data collection through interviews, observations, photos, and videos. data or information related to learning in SD Muhammadiyah 5 Porong. This research method uses descriptive qualitative research methods. The process of learning activities in Indonesia at this time during the COVID-19 pandemic is changing. In the current state of the Covid-19 pandemic, which continues to spread, the government has decided to replace face-to-face learning with bold learning to break the chain of the spread of the Covid-19 virus. at Muhammadiyah 5 Porong Elementary School. The online learning of courage has several obstacles. However, students must still be able to motivate themselves to learn to be brave. Motivation for students during this pandemic has an effect on encouragement from outside, for example encouragement from parents and teachers so that students can learn to study even though they are studying at home.